1995
DOI: 10.1071/ea9951141
|View full text |Cite
|
Sign up to set email alerts
|

Annual ryegrass and volunteer cereal control in lupins using selective post-emergent herbicides

Abstract: The relative effectiveness of herbicides from the aryloxyphenoxypropionate (fop) and cyclohexanedione (dim) chemical families for the control of volunteer wheat (Triticum aestivum L.), oats (Avena sativa), triticale (Triticum x Secale) and annual ryegrass (Lolium rigidum Gaud.) in narrow-leafed lupins (Lupinus angustifolius) were evaluated over a 3-year period near Rutherglen in north-eastern Victoria. Herbicides tested included diclofop-methyl, fluazifop-pethyl, haloxyfop, propaquizafop, quizalofop-p-ethyl, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There are few selective POST herbicides for controlling cereal volunteers in cereals, but herbicides for grass weed control and other volunteer cereals are expected to be effective in broadleaf crops. Chambers et al (1995) reported that a number of aryloxyphenoxypropionate and cyclohexandione herbicides effectively controlled volunteer winter triticale in Australia. Bushong et al (2011) reported that POST glyphosate, clethodim, and quizalofop were effective on volunteer winter wheat in glyphosate‐resistant winter canola in Oklahoma.…”
mentioning
confidence: 99%
“…There are few selective POST herbicides for controlling cereal volunteers in cereals, but herbicides for grass weed control and other volunteer cereals are expected to be effective in broadleaf crops. Chambers et al (1995) reported that a number of aryloxyphenoxypropionate and cyclohexandione herbicides effectively controlled volunteer winter triticale in Australia. Bushong et al (2011) reported that POST glyphosate, clethodim, and quizalofop were effective on volunteer winter wheat in glyphosate‐resistant winter canola in Oklahoma.…”
mentioning
confidence: 99%